(untitled) (Research, Society and Development, 2021)
Considering the importance of corn in agribusiness, seed producing companies have been looking for new technologies to improve seed quality and production, mainly regarding the supply of boron. For that matter, the objective was to evaluate the response of two strains of corn to the application of foliar fertilizer with the Brandt® Manni-Plex® B-Moly technology and the financial viability of this product. The work was carried out in 4 commercial corn seed production areas of Limagrain® Brazil Business Corporation. The hybrid H1 (areas 1 and 3) and hybrid H2 (areas 2 and 4) were tested, with the application of Manni-Plex® B-Moly in the dosage of 1,5 L.ha-1, in stages V7 and VT. As a control, it was used the company’s standard treatment (3 applications of 0,5 Kg.ha-1 of foliar fertilizer with boron in the stages of V4, V10 and VT). In each area the treatments were implanted in bands, considering a completely randomized design, with four repetitions. For the weight of 1000 seeds, number of grains per ear and finished product (60,000 seeds per hecare), the use of the Manni-Plex® B-Moly foliar fertilizer, when compared to the standard treatment, provided average increments of 3,5; 20,5 and 20,4% in H1, and 3,3; 10,0 and 10,0% in H2. The improvement in these production parameters resulted in an average increase of 8,6% in the profitability rate in H1 and 2,0% in H2, indicating that the Manni-Plex® B-Moly technology is efficient in improving corn production components, and consequently, the financial viability guaranteeing better cost benefit for the culture.